Meaningful Memory? Eighteen-Month-Olds Only Remember Cartoons With a Meaningful Storyline - Sonne, Trine; Kingo, Osman S.; Krøjgaard, Peter (Frontiers in Psychology, 2018)
In two studies we investigated the importance of a storyline for remembering cartoons across a delay of two weeks in 18-month-old infants by means of the Visual Paired-Comparison (VPC) paradigm. In Study 1 seventy-one 18-month-olds were tested using similar cartoons as in a recent study from our lab while varying the richness of the storyline information. In a VPC task half of the infants watched uncompromised versions of the cartoons used in the recent study (Storyline Condition), whereas the other half watched Pixelized versions of the cartoons (number of pixels reduced by 98% covering up the narrative, but leaving perceptual details, e.g., colors, movements, the same, Pixelized Condition). Two weeks later they were presented with the familiar cartoon and a novel cartoon from the same version (Storyline or Pixelized) simultaneously, while being eye-tracked. Results showed that only the infants in the Storyline Condition remembered the target cartoon, thus suggesting that the storyline is important for memory. However, an alternative interpretation of the results could be that what made the infants in the Storyline Condition remember the target cartoon was not the storyline, but the static conceptual information of the objects and agents present in the cartoon (which was not visible in the Pixelized version). To test this possibility, a control study was created. In Study 2 thirty-six infants were therefore presented with a version of the cartoon in which we broke down the temporal presentation into 1 second segments and presented these out of order. This was done to preserve the static conceptual information (e.g., objects and agents) while still disturbing the storyline. Results showed that the infants in this condition still did not remember the target cartoon, suggesting that the meaningfulness of the storyline – and not only static conceptual information - is important for later memory.